Pengaruh Cash Ratio, Return On Assets, Firm Size, dan Debt To Equity Ratio terhadap Dividend Payout Ratio: Studi pada Perusahaan Manufaktur Sub Sektor Otomotif dan Komponen yang Terdaftar di BEI periode 2017-2021 - Muchammad Andi Muhaimin; Sriyono; Detak Prapanca (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research determines the influence of Cash Ratio, Return On Assets, Firm Size, and Debt To Equity Ratio on Dividend Payout Ratio. The sample for this research was taken from 10 Automotive and Component Sub-Sector Manufacturing companies listed on the IDX for the 2017-2021 period. Then, this research uses quantitative methods with descriptive statistical calculation techniques and linear regression analysis. The existing data was processed using Eviews software version 12. The research results show that Cash Ratio, Return on Assets, Firm Size do not affect the company's Dividend Payout Ratio. Conversely, the Debt to Equity Ratio affects the Company's Dividend Payot Ratio.